A producer survey on implementation of precision livestock farming in the broiler industry - Terrilyn Klingberg; Robert Burns; Shawn Hawkins; Yang Zhao; Tanner Thornton; Susan Schexnayder (Journal of Applied Poultry Research, 2025)
Summary: While Precision Livestock Farming (PLF) offers many potential benefits for broiler producers, the adoption of PLF on U.S. broiler farms has been limited. Determining the status of PLF implementation in the U.S. broiler industry can aid researchers in developing technology better suited to producer needs to potentially increase PLF field adoption. A survey was sent to 531 broiler producers in Tennessee, U.S. This survey was designed to gather detailed information about current PLF implementation on broiler farms, producer interest in specific PLF technology types, and their willingness to adopt PLF into their production operations. The survey included questions about the current use of fifteen specific PLF tools, the importance of real-time data in their operation, planned use of PLF tools, their goals for using PLF, their willingness to participate in a PLF cost-share program, and their trust in data security. This survey identified a lack of familiarity with PLF among broiler producers, but that they would be willing to adopt PLF if it proved to increase farm productivity and profitability.